Volatile compounds other than CO2 emitted by different microorganisms promote distinct posttranscriptionally regulated responses in plants. (18th December 2018) - García‐Gómez, Pablo; Almagro, Goizeder; Sánchez‐López, Ángela María; Bahaji, Abdellatif; Ameztoy, Kinia; Ricarte‐Bermejo, Adriana; Baslam, Marouane; Antolín, María Carmen; Urdiain, Amadeo; López‐Belchi, María Dolores; López‐Gómez, Pedro; Morán, José Fernando; et al.
Abstract: A "box‐in‐box" cocultivation system was used to investigate plant responses to microbial volatile compounds (VCs) and to evaluate the contributions of organic and inorganic VCs (VOCs and VICs, respectively) to these responses. Arabidopsis plants were exposed to VCs emitted by adjacent Alternaria alternata and Penicillium aurantiogriseum cultures, with and without charcoal filtration. No VOCs were detected in the headspace of growth chambers containing fungal cultures with charcoal filters. However, these growth chambers exhibited elevated CO2 and bioactive CO and NO headspace concentrations. Independently of charcoal filtration, VCs from both fungal phytopathogens promoted growth and distinct developmental changes. Plants cultured at CO2 levels observed in growth boxes containing fungal cultures were identical to those cultured at ambient CO2 . Plants exposed to charcoal‐filtered fungal VCs, nonfiltered VCs, or superelevated CO2 levels exhibited transcriptional changes resembling those induced by increased irradiance. Thus, in the "box‐in‐box" system, (a) fungal VICs other than CO2 and/or VOCs not detected by our analytical systems strongly influence the plants' responses to fungal VCs, (b) different microorganisms release VCs with distinct action potentials, (c) transcriptional changes in VC‐exposed plants are mainly due to enhanced photosynthesis signaling, and (d) regulation of some plant responses to fungal VCs is primarily posttranscriptional. Abstract : Using a "box‐in‐box" test system, here, we have conducted studies to address the question of whether volatile compounds (VCs) from different microorganisms can promote distinct responses in plants. In addition, we evaluated the contribution of microbial organic and inorganic VCs (VOCs and VICs, respectively) in these responses by performing comparative analyses of plants' responses to CO2, complex mixtures of VICs and VOCs, and VOCs‐depleted (VICs‐containing) VCs from two fungal phytopathogens. Our results show that respiratory CO2 plays only a minor role in plant responses to microbial VCs and present evidence that mixtures of VICs from different microorganisms can promote growth and distinct developmental changes in plants. We also provide evidence that (a) the transcriptional changes occurring in plants exposed to microbial VCs are indirectly due to enhanced photosynthesis, and (b) plants' responses to fungal VCs are primarily regulated at the posttranscriptional level.